STEALTH MARKETING TECHNIQUES AND THEIR ROLE IN ATTRACTING CUSTOMERS AND REDUCING COSTS - Khudhur Abbas Jabbar Aefri; Sadeq Dhahir Farhan Alzaidi; Hussein Falah Hasan (Scholar Express Journals, 2024)
The era of globalization and modern technology is witnessing a change in customers' behavior and methods of searching for products, services, and decision-making. These changes require the economic unit to adapt to this change, because traditional marketing methods, such as costly TV ads that have become useless and do not reap the benefits of increasing sales volume and lack the excitement and motivation to attract the customer's attention. Advancing technology and using the Internet and social media has changed customers' habits, making traditional marketing methods often ineffective. With growing customer knowledge and awareness, influencing them has become less effective using costly traditional marketing methods. In order to promote accurate and targeted communication and marketing messages, economic units have begun to search for sophisticated methods that have the potential to influence their behavior. stealth marketing techniques may be the perfect solution. This strategy focuses on influencing customers without explicitly perceiving them, and relies on different techniques to spread promotional messages unaware and appears to be a natural interaction with the target audience and at lower marketing costs. For the purpose of answering the questions and hypotheses of this study, researchers designed a two-item questionnaire: item one is concerned with the variable of hidden marketing techniques, and item two is concerned with the variable of customer attraction and cost reduction. Some customers shopping at the mall have been selected. The results of the study showed the presence of significant relationship between stealth marketing techniques on the one hand and attracting customers and reducing costs on the other.
Keywords: Stealth marketing; Marketing techniques